2010
DOI: 10.1111/j.1462-2920.2010.02277.x
|View full text |Cite|
|
Sign up to set email alerts
|

Soil bacterial diversity in the Arctic is not fundamentally different from that found in other biomes

Abstract: The severe environmental stresses of the Arctic may have promoted unique soil bacterial communities compared with those found in lower latitude environments. Here, we present a comprehensive analysis of the biogeography of soil bacterial communities in the Arctic using a high resolution bar-coded pyrosequencing technique. We also compared arctic soils with soils from a wide range of more temperate biomes to characterize variability in soil bacterial communities across the globe. We show that arctic soil bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

80
408
20
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 548 publications
(525 citation statements)
references
References 42 publications
80
408
20
2
Order By: Relevance
“…For example, soil pH significantly influences both microbial community composition (Fierer and Jackson 2006;Männistö et al 2007;Lauber et al 2009) and abundance in soils (Kolb 2009;Rousk et al 2010), including Arctic soils. Further, Chu et al (2010) reported microbial species diversity and pH can follow an inverted U shape, which is a similar to abundance patterns observed here. However, such observations do not provide a mechanistic explanation for specific geochemical influences on soil microbial conditions; whereas new data here show that explicit soil forming processes and differences in soil mineralogy significantly correlate with local pH and P on regional scale, which in turn, significantly correlates with both bacterial and Type I gene abundances.…”
Section: Regional Geology and Soil Geochemistrysupporting
confidence: 66%
“…For example, soil pH significantly influences both microbial community composition (Fierer and Jackson 2006;Männistö et al 2007;Lauber et al 2009) and abundance in soils (Kolb 2009;Rousk et al 2010), including Arctic soils. Further, Chu et al (2010) reported microbial species diversity and pH can follow an inverted U shape, which is a similar to abundance patterns observed here. However, such observations do not provide a mechanistic explanation for specific geochemical influences on soil microbial conditions; whereas new data here show that explicit soil forming processes and differences in soil mineralogy significantly correlate with local pH and P on regional scale, which in turn, significantly correlates with both bacterial and Type I gene abundances.…”
Section: Regional Geology and Soil Geochemistrysupporting
confidence: 66%
“…Given strong phylogenetic conservatism, broadly resolved data may be well-suited for the detection and interpretation of prokaryotic community dynamics, especially in studies covering broad sampling scales with clear environmental variability. In fact, the original studies of cases #1 and #2 have reported strong correlations between relative abundances of dominant phyla/classes and soil pH (Lauber et al, 2009;Chu et al, 2010). In addition to the spatial variation, the prokaryotic communities might be also sensitive to the seasonal variation, and this temporal dynamics might be also well represented by broadly resolved data.…”
Section: Discussionmentioning
confidence: 98%
“…Sequence-based prokaryotic community data sets We used eight data sets: (1) Lauber 'America-Soils' study (Lauber et al, 2009) (referred to as case #1 hereafter), (2) Chu 'Arctic-Soils' study (Chu et al, 2010) (referred to as case #2 hereafter), (3) Ramirez 'NYpark-Soils' study (Ramirez et al, 2014) (referred to as case #3 hereafter), (4) Zarraonaindia 'NYfarmSoils' study (Zarraonaindia et al, 2015) (referred to as case #4 hereafter), (5) Sunagawa 'TaraSur-Seawaters' study (Sunagawa et al, 2015) (referred to as case #5 hereafter), (6) Sunagawa 'TaraChl-Seawaters' study (Sunagawa et al, 2015) (referred to as case #6 hereafter), (7) Gilbert 'WEC-Seawaters' study (Gilbert et al, 2012) (referred to as case #7 hereafter) and (8) Yeh 'SECS-Seawaters' study (Yeh et al, 2015) (referred to as case #8 hereafter) to test our theoretical framework regarding how the strength of communityenvironment relationships varies with changes in taxonomic resolution (Figure 1). We summarize the characteristics of these sequence-based prokaryotic community data sets in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Even though it is highly unlikely that we have surveyed the full extent of diversity in the treated soils, previous studies suggest that we can quantitatively compare overall community composition and general diversity patterns among different treatments using bar-coded pyrosequencing (Shaw et al, 2008;Chu et al, 2010;Rousk et al, 2010). Here we repeatedly refer to the succession of microbial community.…”
Section: Discussionmentioning
confidence: 99%